Cerebellar transcranial direct current stimulation in patients with ataxia: A double‐blind, randomized, sham‐controlled study. Issue 12 (14th August 2015) - Benussi, Alberto; Koch, Giacomo; Cotelli, Maria; Padovani, Alessandro; Borroni, Barbara
ABSTRACT Background and Objective Numerous studies have highlighted the possibility of modulating the excitability of cerebellar circuits using transcranial direct current stimulation. The present study investigated whether a single session of cerebellar anodal transcranial direct current stimulation could improve symptoms in patients with ataxia. Methods Nineteen patients with ataxia underwent a clinical and functional evaluation pre‐ and post‐double‐blind, randomized, sham, or anodal transcranial direct current stimulation. Results There was a significant interaction between treatment and time on the Scale for the Assessment and Rating of Ataxia, on the International Cooperative Ataxia Rating Scale, on the 9‐Hole Peg Test, and on the 8‐Meter Walking Time (P < 0.001). At the end of the sessions, all performance scores were significantly different in the sham trial, compared to the intervention trial. Conclusions A single session of anodal cerebellar transcranial direct current stimulation can transiently improve symptoms in patients with ataxia and might represent a promising tool for future rehabilitative approaches.